Hubungan Pembelajaran Daring Dengan Ansietas Pada Mahasiswa Di Masa Pandemi COVID-19 - Rafifah, Zalfa Kamila; Sianturi, Renta; Sari, Wulan; Marta, Adista Fitria; Nurfadilah, Adzqya Rizqi; Wasliyah, Dina Nopita; Ayuanita, Della Putri; Nazhifah, Hana Najla (Universitas Harapan Bangsa Purwokerto, 2023)
The existence of a government policy that requires all Indonesian citizens to stay home and conduct activities such as school and work online can trigger anxiety, especially for nursing students. Anxiety affects student achievement because it tends to cause confusion and differences in perceptions. This study determines the level of anxiety among students about online learning during the COVID-19 pandemic. The method used in writing this article was a literature review using the Google Scholar, Pudmed and Neliti databases. The year of publication is limited to 2012–2022 by using the keywords “level of anxiety OR anxiety”, “online OR online learning”, and “COVID-19”. Of the ten articles that have been analyzed, it shows that many things cause student anxiety, especially during online learning during the COVID-19 pandemic. It can be concluded that online lectures are the most frequently mentioned by research subjects causing anxiety but online lectures are an effective learning system during the COVID-19 pandemic.